Development of a Google Sites-Based Photography Portfolio Information System to Improve Vocational High School Students' Skills and Creativity - Hendriana Oktora; Dwi Widjanarko; Ade Novi Nurul Ihsani (Journal of Vocational and Career Education, 2026)
Photography learning in vocational high schools (SMK) with Visual Communication Design (DKV) expertise requires mastery of technical skills and visual creativity supported by a structured portfolio system. However, the management of students' photographic works is still not systematic and not integrated with learning, resulting in low motivation, limited collaboration, and minimal feedback. This study aims to develop a Google Sites-based Photography Portfolio Information System (SiPoKaF) and test its feasibility and effectiveness in improving vocational high school students' photography skills and creativity. The study used the Research and Development (R&D) method with the ADDIE model. The research subjects involved 70 grade XI DKV students of SMK Negeri 1 Pringapus who were divided into experimental and control classes. The research instruments included a media and material expert validation questionnaire, an effectiveness questionnaire, and a photography skill and creativity test through a pretest and posttest. Data analysis was carried out using normality tests, homogeneity tests, N-Gain calculations, and independent sample t-tests. The results showed that SiPoKaF was very feasible to use with a media expert score of 4.75 and a material expert score of 4.4. The effectiveness test showed that the N-Gain value of the experimental class was 83.28%, higher than the control class, and the t-test showed a significant difference in learning outcomes after the treatment. This proves that SiPoKaF is effective in improving the photography skills and creativity of vocational high school students.